Thermal and structural properties of compressed earth brick (Laterite soil) - Ruzaimah, Razmana; Abd Halid, Abdullah; Mohammad Soffi, Md Noh; Abdul Zaki, Abd Wahid (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.